2023
DOI: 10.1142/s0218271823420130
|View full text |Cite
|
Sign up to set email alerts
|

The virial theorem for retarded gravity

Abstract: Galaxy Clusters are huge physical systems having a generic size of tens of millions of light years. Thus any modification at the center of the cluster will affect the outskirts only tens of millions of years afterwards. Those retardation considerations seem to be neglected in present day analysis used to estimate the total mass of the galaxy cluster, including those estimates which are based on the virial theorem. The significant differences between the velocities predicted by Newtonian action at a distance th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Here, δ (3) represents a three-dimensional Dirac delta distribution. This particle induces a Newtonian potential given by:…”
Section: A Discrete Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, δ (3) represents a three-dimensional Dirac delta distribution. This particle induces a Newtonian potential given by:…”
Section: A Discrete Modelmentioning
confidence: 99%
“…He calculated [1,2] that the required amount of matter to explain these velocities could be about 400 times greater than that of visible matter, although later adjustments mitigated this discrepancy to some extent. Had Zwicky utilized the concept of retarded gravity in his calculations, this issue might have been resolved without significant complication [3]. In 1959, Volders [4] noted similar discrepancies on a smaller scale within the outer parts of the nearby spiral galaxy M33, where velocities did not follow the expected 1 √ r pattern.…”
Section: Introductionmentioning
confidence: 99%
“…His calculations showed that the amount of matter required to account for the velocities could be 400 times greater than that of visible matter (this was later mitigated somewhat). In a recent paper we showed that the retarded gravity version of the virial theory [8] may yield better estimates of the mass.…”
Section: Introductionmentioning
confidence: 99%
“…He calculated that the amount of matter required to account for the velocities could be 400 times greater than that of visible matter (this was later mitigated somewhat). Of course, if Zwicky would have use the retarded gravity version of the virial theory [43] no significant problem would arise. In 1959, on a smaller galactic scale, Volders observed that stars in the outer rims of a nearby spiral galaxy (M33) do not move as they should [26].…”
Section: Introductionmentioning
confidence: 99%